An enhanced energy efficient routing protocol in wireless sensor networks / Jacky Even Junis - Jacky Even , Junis (2019)
Wireless Sensor Network (WSN), is a network that comprises of hundreds or thousands autonomous wireless sensor nodes that are scattered randomly in a selected area to monitored the desire physical phenomena and relay the information that it acquired wirelessly to the base station. However, these sensor nodes have small amount of energy source due to its small size form factor thus limited energy resource in sensor nodes has become a major problem in WSN. An enhanced energy efficient routing protocol named Distance Selection Cluster Head Protocol (DCHSP) is proposed in this research. This routing protocol improves the energy efficiency in WSN by electing a new cluster head based on the distance of previous cluster heads which will prevents the new appointed cluster head from concentrating in one part of the network area only. In this routing protocol, for a sensor node to be elected as cluster heads, it must have a distance equal or larger than 2 times of cluster range radius (2CRR) to the previous cluster heads. This make the current cluster head to be spread widely across the network area and therefore all the sensor nodes of the cluster will have a fair travel distance to its cluster head which result in reduced of energy usage for data transmission of the sensor nodes to cluster heads. The performance of DCHSP is evaluated by comparing with several existing protocol namely LEACH and SEP using MATLAB simulation tool. All the routing protocols are simulated in this research and evaluated based on several performance parameters namely number of alive nodes, number of dead nodes, average energy of a nodes, number of packets delivered to the base station and the overall energy consumption of the network. The result from the simulation shows that DCHSP has a better performance compared to LEACH and SEP in number of dead nodes, number of alive nodes, average energy of a node, number of packets delivered and overall energy consumption of the network. In the nutshell, DCHSP has a better performance compared to existing protocol based on energy efficiency.